Development of an efficient and sensitive analytical method for the determination of copper at trace levels by slotted quartz tube atomic absorption spectrometry after vortex-assisted dispersive liquid-liquid microextraction in biota and water samples using a novel ligand - Zaman, Buse Tugba; Bakirdere, Emine Gulhan; Kasa, Nursu Aylin; Deniz, Serenay; Sel, Sabriye; Chormey, Dotse Selali; Bakirdere, Sezgin (SPRINGER, 2018)
This study describes the determination of trace levels of copper by slotted quartz tube atomic absorption spectrometry after dispersive liquid-liquid microextraction. A ligand synthesized from the reaction of salicylaldehyde and 1-naphthylamine was used to form coordinate copper complex prior to extraction. All parameters that influence the output of complex formation, extraction, and instrumental measurement were optimized to enhance the absorbance signal of copper. Under the optimum conditions, about 104-fold enhancement in sensitivity was recorded over the conventional flame atomic absorption spectrometer, corresponding to a 0.51 ng/mL detection limit. The percent relative standard deviation calculated for the lowest concentration (4.8%) indicated high precision for the experimental procedure. Accuracy and applicability of the optimum method were determined by performing spiked recovery tests on urine, lake water, and mineral water samples. Satisfactory recovery results were obtained between 82.2 and 106.3% at four different concentrations. Matrix matching method was also performed to increase the accuracy of quantification, and the percent recovery calculated for 175 ng/mL was 105.14%.
Keywords: Copper; FAAS; SQT; DLLME; Urine; Lake and mineral water; MASS-SPECTROMETRY; HYDROPHOBIC PROTEINS; FOOD SAMPLES; MALDI-MS; LEAD; PRECONCENTRATION; CADMIUM; IONS; NANOPARTICLES; EXTRACTION; Environmental Sciences & Ecology